Risk management: enabler for better decision making - Schütt Fiig, Annette (Henry Stewart Talks, 2013)
Risk definition, Enterprise Risk Management (ERM), Embedding Risk Culture as a natural component of the Company DNA, Novo Nordisk risk management structure, Using a framework to help structure the approach, Assessing Risks, The need for internal communication, Training and Keeping momentum